Chestnut blight: an epidemic checked by biological control - LOCCI, ROMANO (Gjornâl Furlan des Siencis - Friulian Journal of Science, 2003)
Chestnut blight is one of the most devastating plant diseases. Within 50 years of its discovery in North America in 1904, mature American chestnut trees (Castanea dentata Borkh.) could only rarely be found within their natural range and the tree now survives only as sprouts growing from stumps of trees attacked by the blight. The disease was then introduced into Europe where it caused considerable damage in the local chestnut (Castanea sativa Mill.) plantations. However the development of biocontrol techniques, based on natural recovery of diseased plants, has prevented the extinction of the European chestnut. The history of the epidemics, the use of hypovirulent strains of the pathogen for biological control and the work carried out by the author and his co-workers are reviewed and discussed.